The association between albumin and mortality in patients with acute kidney injury: a retrospective observational study - Kaibi Yang; Nan Yang; Wenbo Sun; Limiao Dai; Juan Jin; Juan Wu; Qiang He (BMC Nephrology, 2023)
Abstract Background While the association between decreased serum albumin (ALB) levels and increased risk of acute kidney injury (AKI) is well established, the risk of death among patients with AKI with low serum ALB levels is unclear. We aimed to evaluate the association between serum ALB levels in patients with AKI and mortality, and help guide their clinical management. Methods The included patients were those diagnosed with AKI and admitted to Zhejiang Provincial People's Hospital between January 2018 and December 2020. The clinical endpoint was all-cause mortality rate at 90-days and 1-year. Patients were divided into four groups according to the quartiles (Qs) of ALB measurements at admission. Cumulative survival curves were calculated using Kaplan–Meier analysis, and Cox proportional risk models were used to assess the association between serum ALB levels and 90-day and 1-year all-cause mortality. Results This study included 740 patients with AKI. Patients with measured ALB values were classified into quartiles: Q1 ≤ 26.0 g/L (n = 188); Q2 = 26.1–30.5 g/L (n = 186); Q3 = 30.6–34.7 g/L (n = 183); Q4 ≥ 34.8 g/L (n = 183). Univariate analysis using Cox regression showed that for every 10 g/L increase in ALB, the 90-day and 1-year mortality decreased by 29%. Among the four subgroups, patients with lower ALB levels had a higher risk of death. After adjusting for demographics, comorbid conditions, inflammatory index, and medicine, the lowest ALB quartile (ALB < 26 g/L) was associated with increased risk of 90-day mortality (hazard ratio [HR], 1.76; 95% confidence interval [CI], 1.30 to 2.38, P < 0.001) and 1-year all-cause mortality (HR, 1.79; 95% CI, 1.33 to 2.41, P < 0.001). Conclusions ALB levels in patients with AKI were significantly correlated with prognosis, and the higher the level, the better the prognosis. Compared to patients with ALB ≥ 34.8 g/L, patients with 26.1 g/L < ALB ≤ 30.5 g/L had an increased risk of 90-day and 1-year all-cause mortality of approximately 40%, and patients with ALB ≤ 26.0 g/L had an increased risk of 90-day and 1-year all-cause mortality of approximately 76% and 79%, respectively.